2019
DOI: 10.1073/pnas.1909886116
|View full text |Cite
|
Sign up to set email alerts
|

Artificial turf infill associated with systematic toxicity in an amniote vertebrate

Abstract: Artificial athletic turf containing crumb rubber (CR) from shredded tires is a growing environmental and public health concern. However, the associated health risk is unknown due to the lack of toxicity data for higher vertebrates. We evaluated the toxic effects of CR in a developing amniote vertebrate embryo. CR water leachate was administered to fertilized chicken eggs via different exposure routes, i.e., coating by dropping CR leachate on the eggshell; dipping the eggs into CR leachate; microinjecting CR le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…42 Another study exposed chicken embryos to tire crumb leachate and documented a variety of adverse effects from exposure to the chemical mixture. 43 For illustrative purposes, additional detail is provided here on selected chemical categories.…”
Section: Resultsmentioning
confidence: 99%
“…42 Another study exposed chicken embryos to tire crumb leachate and documented a variety of adverse effects from exposure to the chemical mixture. 43 For illustrative purposes, additional detail is provided here on selected chemical categories.…”
Section: Resultsmentioning
confidence: 99%
“…For example, TP leachate exposure caused severe development malformation of amniote vertebrate. 45 TP Amendment Decreased the Survival and Reproduction Rate of Worms. TP exposure had a dose-dependent effect on the reproduction of worms (Figures 1 and S5).…”
Section: ■ Discussionmentioning
confidence: 97%
“…Multiple studies have reported toxic potency of tire rubber leachate to algae, anthropods, molluscs, fish, and vertebrate embryos . The rubber vulcanizing agent, N,N′-diphenylguanidine (DPG) has been reported to be a highly abundant feature identified by nontarget analysis in road runoff. , DPG has measured acute (48 h LC 50 ) and chronic (21 day) toxicities of 17 and 0.6 mg L –1 (daphnia) .…”
Section: Introductionmentioning
confidence: 99%